Deepfake Dilemmas: Imagine Tomorrow’s Surveillance Society through Three Scenarios - Fatma Doğan Akkaya (Istanbul University, 2024)
As deepfakes—hyperrealistic, manipulated media content becomes increasingly sophisticated, they raise critical questions about the future of social interaction and trust. Drawing on sociological insights enriched by the literature on virtual reality surveillance, this study explores the social landscapes that may emerge with the widespread adoption of deepfake avatars in the near future. Moving beyond technical considerations, the research employs social prediction methods to explore three potential future scenarios involving deepfake avatars: seamless integration that facilitates self-expression but complicates digital identity control; pervasive algorithmic surveillance that exacerbates social control and privacy issues; and the concept of ghost avatars, that is, digital representations that function as commodities or tools of resistance. This analysis highlights the ethical dilemmas surrounding deepfakes, particularly in relation to mass surveillance, digital self-control, and resistance movements. Contributing to scholarly discourse, the study underscores the need for proactive social and ethical frameworks to navigate the evolving deepfake landscape and highlights the importance of ongoing research for the responsible development and use of this powerful technology.
Keywords: digital society; future scenarios; Sociology (General); artificial intelligence (ai); deepfake technology; virtual surveillance; HM401-1281